(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the efficacy of a homeopathic anthelmintic drug in Santa Inês sheep naturally infected by gastrointestinal parasites. We used 15 Santa Inês lambs, weaned, males, neutered, aged between 50 and 60 days, weighing between 20 and 30 kg, randomly distributed in a completely randomized design with 3 experimental treatments and 5 replicates each, control treatment, where the animals did not receive medication; homeopathic treatment; and oral allopathic treatment for 90 days. The number of nematode eggs in faeces (OPG), dry matter consumption, weight gain, feed conversion, hot carcass yield, cold carcass yield, cooling loss, hot carcass weight and cold carcass weight were evaluated. The treatment of sheep for three months with different anti-helminthics did not present a statistically significant difference (p>0.05) in relation to OPG of the treated groups. There was no effect (p>0.05) on variables, feed conversion, hot carcass yield, cold carcass yield, cooling loss, cold carcass weight and hot carcass weight. It was found that the treatment using the homeopathic product obtained a higher consumption of dry matter, resulting in greater daily weight gain. The application of the homeopathic medicine used in the present study is feasible in the production of Santa Inês sheep because it presents results similar to allopathic treatment and does not impair the performance of the animal.